Sosialisasi Terhadap Perundungan Sekolah Dasar Negeri No. 101798 Kecamatan Deli Tua, Deli Serdang - Nirmawan Mawan; Astirima Rima Asti; Auryel Arkan Alifi; Ade Nabilla Yushifa Rahma; Fatimah Timah; Rinanda Sri Rezeki; Syainda Dewi Syifa Pohan; Dea Ananda; Muhammad Arya Adyva (Universitas Teuku Umar, 2025)
Bullying in the elementary school environment is a serious problem that requires comprehensive handling. This community service activity aims to provide education and understanding about bullying prevention through socialisation at SDN 101798 Deli Tua. Based on initial observations, all grade 5 students (100%) reported having experienced verbal bullying from peers. The socialisation activity was carried out using descriptive qualitative methods in the form of lectures, discussions and questions and answers conducted in December 2024 involving 30 grade 5 students. The material presented included the definition of bullying, forms of bullying, the impact and how to overcome it. The results of the activity showed three main achievements: students did not repeat bullying behaviour and understood the dangers, increased self-confidence of students who had been victims of bullying, and increased student insight into bullying which contributed to the creation of a safer school environment. This activity proves that structured and interactive socialisation can increase students' awareness about the dangers of bullying. Regular evaluation and active collaboration between schools and parents are needed to ensure the sustainability of the results of this socialisation programme.